Parricide and violence against parents : a cross-cultural view across past and present - Muravyeva, Marianna; Shon, Phillip C.; Toivo, Raisa Maria (New York : Routledge, 2021)
"The book provides a synthesis of parricide and violence against parents across the past and present. Taking a historical and criminological approach, this book places fatal and non-fatal violence against parents in the context of social development from the 1500s to contemporary society and provides global overview and comparison across the world. The book collects evidence on a seemingly rare subject from different eras, areas and cultures, and then uses the cross-disciplinary data to produce new, systematic insight. This book provides an examination of parricide and violence against parents that is historically and culturally sensitive. A historical approach to parricide and violence against parents illuminates the variations in conflicts between parents and their offspring that are shaped by the life stages of the victims and offenders themselves across time. As criminologists have noted, abuse is an important factor in parricides. However, the very definition, practice, and meaning of discipline and punishment have evolved throughout history. By moving away from the analytical scrutiny on child abuse and mental illness as implicative factors in parricide, a historical approach to parricide and violence against parents objectifies these types of cultural shifts over time as warrantable topics of enquiry. This book shows that inheritance customs and laws affect the social organization of families in significant ways. Using illustrative case studies, this book shows how aging parents used their inheritance as a leverage and as a social safety net to ensure stability and security in their old age, enticing various family members and complete strangers to serve as caretakers in ways that reconfigured the composition of households. It appeals to numerous subject areas such as criminology, history of crime, history of the family, family violence, homicide studies, gender studies, history of emotions, political violence, and social work. It is precisely relevant because it fills in a glaring gap in the market on the history of parricide and violence against parents. Furthermore, rather than treating violence against parents as a simple illustration of age-related violence, the book nestles age-graded violence against the parents within the context of family life, as parents and offspring negotiate the valleys and peaks of the life cycle"--
OCLC-licensed vendor bibliographic record.
Keywords: Parricide -- History; Parents -- Violence against -- History; Family violence -- History; HISTORY / Social History; PSYCHOLOGY / Social Psychology; SOCIAL SCIENCE / Criminology